PREVALENCE OF GESTATIONAL DIABETES MELLITUS IN AN URBAN INDIAN COHORT USING DIABETES IN PREGNANCY STUDY GROUP IN INDIA (DIPSI) CRITERIA – VALIDATING ONE-STEP APPROACH - Khan, S.; Bal, H.; Khan, I. D.; Paul, D. (International Journal of Medicine and Medical Research, 2019)
Background. India is the “World’s Diabetes capital”, with half the diabetic population being women. Early detection of glucose intolerance during pregnancy offers a timely opportunity for screening, management and prevention of gestational diabetes mellitus (GDM) and prevents fetal complications. Objective. The study assessed the prevalence of GDM in an Indian cohort using the Diabetes in Pregnancy Study group of India (DIPSI) criteria. Methods. 200 pregnant women underwent two-phase testing with non-fasting 75-gram glucose challenge under Diabetes in Pregnancy Study group of India (DIPSI) criteria at <20 weeks and between 24-28 weeks period of gestation. A 3-hour 100-gm oral glucose tolerance test (OGTT) was used for confirmation. Repeat testing was done for women negative during the first-phase. Results. Mean age was 24.26±3.75 years with 52.5% multigravidas. Mean Body Mass Index (BMI) was 20.7±3.07 kg/m2. The prevalence of GDM in study cohort was found to be 15.5% using the DIPSI criteria while the prevalence of GDM after 100 g OGTT was 13.0%. GDM was mostly seen to occur in women of 26-30-year age group. Statistically significant associations for age and GDM, and BMI and GDM were evidenced. Conclusions. Maternal age of ≥25 years should be adopted as a risk factor for the development of GDM. The DIPSI criteria offer a cost-effective and an evidence-based protocol for a single-step definitive glucose test for both screening and diagnosis of pregnant patients belonging to any socio-economic strata; furthering its implementation for public health obstetrics.